The scientometric evaluation of the research on the students with ADHD in higher education - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the literature on the students with attention deficit hyperactivity disorders (ADHD) in higher education published during the last three decades and its implications using the scientometric techniques. The study employs the scientometric methods using the databases of SCIE and SSCI. The literature in this field has grown exponentially during this period reaching to 276 papers in total. Papers are mostly journal articles, reviews, and proceedings, predominantly in English. The US is the most publishing country and the "University of Michigan" is the most contributing institution. The most publishing author is "McCabe SE". "Journal of Attention Disorders" is the most publishing journal whilst, "Psychiatry" is the most published subject area. "H-index" is 32 and Logan et al. [1] has had the highest impact on the literature. The scientometric analysis has a great potential to gain valuable insights into the evolution of the research on the students with ADHD in higher education.
Keywords: ADHD; Attention deficit hyperactivity disorders; Higher education; Students; Scientometrics; Research evaluation